2021
DOI: 10.1038/s41598-021-94098-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertilization on protein and carbohydrate fractions of Marandu palisadegrass

Abstract: The effects of nitrogen (N) fertilization levels on protein and carbohydrate fractions in Marandu palisadegrass pasture [Urochloa brizantha (Hochst. ex A. Rich.) R.D. Webster] were investigated in a pasture over five years. The experimental design was completely randomized with four levels of N (0, 90, 180, and 270 kg N ha-1, as urea) for five years, and with three replicates. The study was conducted in a continuously stocked pasture during the forage growing season (December to April) in a tropical region. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
2
13
0
4
Order By: Relevance
“…Specifically, the total CHO content decreased linearly with the increasing levels in suppling nitrogen to the plant ( Table 4 ) on account of the increased use of these carbohydrates to transform the available nitrogen into protein, as a plant natural response [ 72 , 73 ]. Our results are in agreeance with those of Leite et al [ 74 ], who observed low total CHO when the highest nitrogen fertilization rate (270 kg N ha −1 ) applied on Marandu palisadegrass.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, the total CHO content decreased linearly with the increasing levels in suppling nitrogen to the plant ( Table 4 ) on account of the increased use of these carbohydrates to transform the available nitrogen into protein, as a plant natural response [ 72 , 73 ]. Our results are in agreeance with those of Leite et al [ 74 ], who observed low total CHO when the highest nitrogen fertilization rate (270 kg N ha −1 ) applied on Marandu palisadegrass.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the NFC content of black mustard aerial biomass are presented in Table 4 . During the experimental periods, the NFC content exhibited a similar behavior as total CHO content, presenting decreases in its values with the increasing levels of available nitrogen to the plant [ 74 ]. This is also supported and confirmed by the significant and high linear correlation between the CHO and NFC contents ( r = 0.8172, p < 0.001; Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“… 6 in palisade grass pastures N (0 to 270 kg N ha −1 ), which the N-use efficiency ranged from 2.8 to 1.7 kg BW gain per kg N. Martha Jr. et al . 3 based on a review about efficiency of N-use in Brazilian pastures concluded that: an efficiency > 1.8 kg BW gain per kg N is considered good; and > 2.4 kg BW gain per kg N is considered excellent.…”
Section: Discussionmentioning
confidence: 99%
“…In Cerrado regions of Brazil, it is estimated that there are at least 32 million ha of degraded pastures 1 , i.e., areas characterized by a decrease in regrowth vigor, consequently reducing carrying capacity and animal production, which results in great economic and environmental damages. Nitrogen fertilization is essential for maintaining pasture productivity and for its sustainability, since nitrogen deficiency is one of the main factors triggering pasture degradation process 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Além das alterações no teor de PB na forragem e silagens em função dos diferentes manejos, houve também alterações quanto as suas frações. Essa identificação das frações proteicas é importante no sentido de conhecer como essa disposição poderá impactar na degradação ruminal, no crescimento microbiano e por consequência na eficiência de utilização do alimento pelo animal (Leite et al, 2021).…”
Section: Discussionunclassified